Remote maternal-fetal telemedicine monitoring for high-risk pregnancy care: A feasibility study - Jack Le Vance; Alexandra Emms; Victoria Hodgetts Morton; R. Katie Morris; Leo Gurney (PLoS ONE, 2025)
High-risk pregnancies undergo regular antenatal monitoring, including cardiotocography (CTG) and ultrasound. Recently there has been an emergence of sophisticated remote telehealth interventions, potentially enabling care to be shifted into the home setting. Our aim was to evaluate the feasibility and acceptability of home CTG and home ultrasound monitoring for high-risk pregnancies. This was a single center study. Women aged ≥18 years, English speaking, singleton pregnancy, ≥ 32 weeks gestation and had at least one of four high-risk obstetric conditions were eligible. Participants were randomized to one of three groups: (1) home ultrasound; (2) home CTG; and (3) both, whilst continuing their routine antenatal care. The primary outcome was completion of 20 minutes of interpretable fetal heart recording and/or completion of an interpretable fetal ultrasound for each monitoring episode. Ultrasound interpretability was assessed for three validated criteria: fetal heartbeat, fetal movements and liquor volume assessment. Secondary outcomes included monitoring adherence, anxiety management, acceptability and safety. Fifteen participants, within three groups, completed 24 remote ultrasounds and 59 remote CTGs. Overall, the fetal heartbeat, movements and an assessment of the liquor volume were identified in 92%, 83% and 100% of all ultrasound scans respectively. 79% of all scans had all three criteria unanimously assessed. Three-quarters of all CTGs contained at least 20 minutes of continuous interpretable computerized fetal heartrate recording. Neither ethnicity, parity, BMI nor fetal presentation were significant factors for achievement of the primary outcome for both devices. There was non-significant reduction in anxiety scores before and after device usage (p = 0.19). Participants’ monitoring adherence and acceptability ratings were high in all groups. No adverse maternal-fetal outcomes relating to device usage occurred. Home ultrasound and cardiotocography are potentially feasible and acceptable to high-risk pregnant women. Larger studies are required to refine how best to implement such devices into clinical practice. ClinicalTrials ID: NCT06366711.